Aspiration Alone, Aspiration Plus Steroid Injection and Aspiration Plus Ethanol Injection for Treatment of Dorsal Wrist Ganglions: A Comparative Study among Three Methods (Journal of Enam Medical College, 2016)
Background: There are varieties of treatment modalities to treat dorsal wrist ganglion cysts. But none of these has been the standard. So, we designed this study to compare among different treatment modalities.Objective: To compare the effects of aspiration alone, aspiration plus methylprednisone injection and aspiration plus ethanol injection into the dorsal wrist ganglions.Materials and Methods: This prospective study was performed in Dhaka Medical College Hospital, Dhaka from March 2010 to May 2011. Sixty six patients with dorsal wrist ganglions were treated in three groups aspiration alone in 24 patients (Group A), aspiration plus methylprednisolone injection into the cyst in 20 patients (Group B) and aspiration plus ethanol injection, then reaspiration of the ethanol from the cyst after 35 minutes, in 22 patients (Group C). Elastic compression bandage was applied in all patients and recommended for 3 weeks. Follow-up was done at 1, 3, 6 and 12 months and conclusive assessment was done during final visit.Results: The success rate in Group A was seen in 9 patients (37.5%), in Group B in 11 (55%) and in Group C in 14 (63.5%) patients. The most frequent side-effect was pain during ethanol injection which was relieved by reaspiration of cyst.Conclusion: Injection of ethanol into the dorsal wrist ganglion was associated with higher success rate compared to aspiration and methylprednisolone injection. Further studies with larger sample size should be performed to assess the effect of ethanol injection in this disease.J Enam Med Col 2016; 6(1): 19-22